The Effect Of Service Quality, Location, And Brand Image On Customer Decisions To Transact At Bank Maybank Kc Pangkalpinang - Herry Harianto (Economics and Digital Business Review, 2026)
The development of digital banking in Indonesia has significantly changed customer transaction behavior, including at Bank Maybank. Digital services such as M2U and Smart Branch initiatives have encouraged some customers to shift toward online transactions, although many still prefer in-person services at branch offices. This situation requires the bank to identify the factors that influence customers’ decisions to conduct transactions at the branch. This study aims to analyze the influence of service quality, location, and brand image on customer transaction decisions at Bank Maybank KC Pangkalpinang. The population consists of customers who conduct transactions at the branch, and a sample of 100 respondents was selected using a non-probability sampling technique through accidental sampling. Data were processed using quantitative methods, including instrument testing (validity and reliability), classical assumption tests, and multiple linear regression analysis with t-tests and F-tests, using SPSS version 26. The results indicate that: (1) Service quality has a positive and significant effect on customer transaction decisions; (2) Location has no positive and insignificant effect on customer transaction decisions; (3) Brand image has a positive and significant effect on customer transaction decisions; and (4) Service quality, location, and brand image simultaneously have a significant effect on customer transaction decisions at Bank Maybank KC Pangkalpinang.